Spore germination and recurrence of clostridioides difficile infection - Finch, Lorna (2020)
Clostridioides difficile-associated diarrhoea (CDAD) has emerged as a leading healthcare-associated infection of great clinical and economic significance. The infection is not only characterised by debilitating symptoms but is also complicated with a high incidence of recurrence and is increasingly found in the community. C. difficile spores are resistant to many chemical and physical agents, as a result spores shed in faecal matter are very difficult to eradicate, leading to infection, or re-infection, of cohabiting individuals through ingestion of spores from contaminated surfaces. Interventions that target sporulation could, therefore, have an enormous impact on disease transmission. Nonetheless, it is the toxin-producing vegetative cells that subsequently arise following germination that cause disease and so intervention at the stage of germination would be an effective means of disease prevention. In this study various methods where employed towards the elucidation of ribotype prevalence and spore phenotypes of clinical isolates derived from 151 patients enrolled on a trial to assess the use of Rifaximin as a measure to control relapse of Clostridioides difficile infection (CDI). Genomic characterisation of a subset of isolates was performed to differentiate incidence of reinfection from relapse. Pangenome analysis together with genetic variation analysis of 23 key genes implicated in the colonisation, sporulation, germination and outgrowth of C. difficile was conducted to elucidate whether genotypic and phenotypic characteristics of isolates could be implicated as significant virulence or risk factors of recurrence in CDAD. A subset of 35 isolates were presented in this research. In this subset, 23 isolates are from 9 patients, who clinically presented with recurrent CDI, and 12 isolates from 6 patients, who clinically presented with non-recurrent CDI. Specific research questions included, whether variations of spore phenotypes and within the genomes among isolates over the infection period of CDI and recurrence could be observed. To further support associations with data from clinical isolates, sporulation and germination phenotypes where screened by construction and characterisation of insertional ClosTron mutations in CD19300, CD05460, CD07730, CD07750, CD29630, CD08670 and CD24700, seven hypothetical genes, in the non-epidemic C. difficile 630Δerm strain. Targets where proposed to be involved in sporulation and germination pathways, particularly CD24700, encoding the germination protease (GPR). A recombinant GPR was produced to further asses its role along with the crude extraction of acid soluble spore proteins hypothesised to contain the GPR substrates, small acid soluble proteins (SASPs). It was hypothesised that germination and outgrowth redundancies of strains relate to prolonged spore dormancy and persistence and thus these specific phenotypes would act as an explanation/virulence factor of relapse. Whereas reinfection would be predicted to be a result of competitive outgrowth of each co-infecting isolate, where antibiotic activity would disturb the faster outgrowing more so than the slower counterpart. The data collected in this study showed evidence to support these hypotheses. Interestingly, mutations leading to amino acid changes were detected in the germinant receptor, CspC, proline reductase, PrdB and exosporium glycoproteins, BclA1 and BclA3, for all isolates included in further genetic characterisation, whilst the initiation of spore germination was found to be significantly reduced in comparison to reference strain for all clinical isolates tested, indicating a higher level of control for Taurocholate-mediated germination. Additionally, levels of spore dormancy were detected in all clinical isolates tested, indicating the potential for relapse in all isolates. The inactivation of a hypothetical gene, CD24700, hypothesised to encode a germination protease (GPR), was revealed to have significant phenotypes supporting a clear role in spore viability, outgrowth and dormancy. Together, this study has contributed and expanded our knowledge of germination and outgrowth of spores of the non-epidemic C. difficile 630Δerm strain and of clinical isolates. It is hoped that sustained study will reveal further virulence factors of relapse and targets to prevent and tackle recurrent CDI.